THE SAMSARI VOLCANIC CENTER AS AN EXAMPLE OF RECENT VOLCANISM IN THE LESSER CAUCASUS: K-AR GEOCHRONOLOGICAL AND SR-ND ISOTOPIC DATA - Lebedev V.A.; Chernyshev I.V.; Arakelyants M.M.; Bairova E.D.; Gol'tsman Yu.V.; Chugaev A.V.; Dudauri O.Z.; Vashakidze G.T. (My University, 2003)
The isotope–geochronological data obtained reveal a large center of Late Quaternary volcanism in the southern part of Republic of Georgia – Samsari volcanic center, with its main development phases corresponding to phases of magmatic activity previously defined for other areas of neovolcanic activity in the Caucasus region. According to these data, the youngest volcanic events occurred in the terminal Pleistocene–Holocene, which makes this region potentially hazardous with respect to future volcanic activity
Keywords: Cenozoic::Quaternary; Кайнозой::Четвертичная